Influence of simvA glyzin on expression and inhibition of hmg-coa reductase in rats liver - Yu. I. Ragino; V. A. Vavilin; E. M. Stakhneva; N. F. Salakhutdinov; O. G. Safronova; A. B. Shintyapina; V. V. Lyakhovich; Yu. P. Nikitin (Атеросклероз, 2015)
Activity, level of protein and mRNA HMG-CoA reductase were investigated in rats liver treated with simvastatin (SV), its complex compound with glycyrrhizic acid – simvaglyzin (SVG) and glycyrrhizic acid alone. Level of protein HMG-CoA reductase was reduced on 25 % in SVG group (р < 0.05) 24 hours after introduction the last dose. Level of mRNA was significantly increased in experimental group in compared to control. In vitro SVG was uncompetitive inhibitor of HMG-CoA reductase (Ki = 94 nM). SVG gain the inhibitor properties following cytochrome P450-dependent metabolism. The addition of 1mM methyrapone in incubation medium fully prevented the inhibition of 3-HMG-CoA reductase. SV and SVG in concentrations of 300 nM inhibited of mevalonate synthesis rate by 39.15 ± 8.27 % and 38.85 ± 3.04 %, respectively.